Microstructure and mechanical properties of accumulative roll bonded aluminium alloy AA5754 - Hausöl, Tina; Höppel, Heinz Werner; Göken, Mathias (Journal of Physics: Conference Series, 2010)
The aluminium alloy AA5754 is used for many technical applications. In this work, the accumulative roll bonding process is applied to this alloy in order to investigate the potential of an ultrafine-grained structure on the mechanical properties of this Al-Mg alloy. Sheets from AA5754 (AlMg3) were successfully processed by accumulative roll bonding in order to obtain an ultrafine-grained microstructure. The ARB process was performed at 230 °C or 250 °C up to 7 or 8 cycles respectively. Thus the grain size decreased from 10 extgreekmm (initial state) to approximately 80 nm (ultrafine-grained state, normal direction). The microstructural evolution and the mechanical properties have been investigated by means of scanning electron microscopy, hardness measurements and tensile testing. After one ARB cycle the samples showed an increase in hardness by a factor of almost 2 in comparison to the as-received material. Further processing causes a linear increase of hardness with each additional cycle. Yield strength and tensile strength of the roll bonded specimens are highly increased in comparison to the as-received samples whereas the ductility declined. A considerable increase in ductility is obtained by heat treatment of the ARB specimens at 250 °C, but on the expense of a moderate decreased strength. The deformation behaviour is also influenced by the ultrafine-grained structure. The occurrence of the Portevin-Le Chatelier effect is manifested by serrated stress-strain curves. The amplitude of serrations increases with increasing number of ARB cycles but can be reduced by the appliance of a higher strain rate. Lüders strain only occurs at the as-received, i.e. not strained, samples.
EAM Import::2019-03-12